ANALISIS AKAD-AKAD DALAM FINTECH P2P LENDING SYARIAH DI INDONESIA - Gilang Arvianto; Marlon Boderingan Cortez; Vela Retna Widyastuti; Zulan Ilmada (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The purpose of this study is to explain and analyze Islamic Fintech P2P Lending contracts in Indonesia. This research method is using a qualitative approach. Data collection techniques using literature study. The data validity technique of this research uses data triangulation techniques. The results of this study are an explanation and analysis of the contracts used in Islamic Fintech P2P Lending in Indonesia. The conclusion of this study is the advantages and disadvantages of Islamic Fintech P2P Lending contracts. This research provides a solution related to the shortcomings that exist in Islamic Fintech P2P Lending contracts. The implications of this research can be used as knowledge for the wider community who want to use Sharia Fintech P2P Lending.Keyword: Sharia Fintech; Sharia Fintech Contracts; Sharia Financing